PENERAPAN MODEL PENEMUAN TERBIMBING UNTUK MENINGKATKAN MOTIVASI, KETERAMPILAN PROSES SAINS, DAN HASIL BELAJAR PADA KONSEP GETARAN, GELOMBANG, DAN BUNYI DI KELAS VIII.2 SMPN 01 KOTA BENGKULU - Diatri Novita; Connie Connie; Eko Risdianto (Kumparan Fisika, 2017)
The purpose class act  research are to know how to upgrading, motivate students to learn, skill of science process and the result of students at class VIII2 SMPN 01 Kota Bengkulu for frequency, wave, sound already 4 cycles. The subjects of research there are 33 students. The result of research show us the upgraded student’s study activity for every cycles are 21 (cyle I) , 23.5 (cyle II) , 27.5 (cyle III) and 29 (cyle IV). The upgrading of students motivation every indicator of  motivation by cyle I to cyle IV. The indicator of students desire is 25.82 (cyle I) to be 28.6 (cyle IV). The indicator of appreciation to learn is 17.79 (cyle I) to be 19.6 (cyle IV) . the indicator of interest activity of learn is 22.15 (cyle I) to be 24.21 (cyle IV)  finally indicator of study area which condusive so that make student learn more is 18.18 (cyle I) to be 19.67 (cyle IV). Skill of science process show upgrade to show average every aspect skill of science process. Aspect clasification is 64.85 (cyle I), 70.3 (cyle II), 82.25 (cyle III), 92.5 (cyle IV). Aspect hypotesis formula are 54 (cyle I), 79.65 (cyle II) , 80.35 ( cyle III)  and 87.5 (cyle IV). Aspect instrument uses are 82 (cyle I) , 92.95 (cyle II), 93.75 (cyle III), and 95.5 (cyle IV) and 80.35 (cyle IV). The result of study to knowledge aspect rise to completness study as classical 59.4 % (cyle I) not complete as classical is 92.8 % (cyle III) in complete classical and 100% (cyle IV) complete as classical.